2015
DOI: 10.1021/jp510347r
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Dependence of Pd Nanocrystal Carburization during Acetylene Hydrogenation

Abstract: This interdisciplinary work combines the use of shape-and size-defined Pd nanocrystals (cubes of 10 and 18 nm, and octahedra of 37 nm) with in situ techniques and DFT calculations to unravel the dynamic phenomena with respect to Pd reconstruction taking place during acetylene hydrogenation. Notably, it was found that the reacting Pd surface evolved at a different pace depending on the shape of the Pd nanocrystals, due to their specific propensity to form carbides under reaction conditions. Indeed, Pd cubes (Pd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 52 publications
1
42
0
Order By: Relevance
“…Since the reaction energy of C 2 H 2 decomposition to produce 2C + 2H are more negative on Pd(100) than Pd(111), it can be concluded that the overall reaction barrier of carbon atom production should be lower over Pd(100). These results are in good agreement with the experimental results reported very recently, that acetylene reacts much faster with Pd(100) to form Pd carbide than with Pd(111) surface [40].…”
Section: Resultssupporting
confidence: 93%
“…Since the reaction energy of C 2 H 2 decomposition to produce 2C + 2H are more negative on Pd(100) than Pd(111), it can be concluded that the overall reaction barrier of carbon atom production should be lower over Pd(100). These results are in good agreement with the experimental results reported very recently, that acetylene reacts much faster with Pd(100) to form Pd carbide than with Pd(111) surface [40].…”
Section: Resultssupporting
confidence: 93%
“…The negative shift of the reflection peak indicates that C is incorporated into Pd atoms, which induces lattice expansion. The lattice expansion (lattice parameter, a) is in proportion to the fraction of guest atoms (x = C/Pd), as expressed by the following equation [71]: a = a 0 + 0.69x (Å). Therefore, the x value of the m-PdAuAg 2 catalyst is 0.028, approximately double that of the cPdAuAg 2 catalyst.…”
Section: Influence Of Catalyst Morphology On Selectivitymentioning
confidence: 99%
“…The most widely adopted process for acetylene removal is selective hydrogenation over supported Pd‐based catalysts 1, 2. In addition to its great industrial significance, this reaction has been frequently used as a model reaction for theoretical investigation 3–7, e.g., rational design of heterogeneous catalysts 8–10, testing new in situ characterization methods 11–16 etc.…”
Section: Introductionmentioning
confidence: 99%